2005
DOI: 10.1590/s0001-37652005000200004
|View full text |Cite
|
Sign up to set email alerts
|

Golden mussel Limnoperna fortunei (Bivalvia: Mytilidae) distribution in the main hydrographical basins of Uruguay: update and predictions

Abstract: Limnoperna fortunei, an Asiatic rivers bivalve has become a worldwide problematic invasive species causing several water quality and macrofouling problems. In the Neotropical region it was first recorded in 1991 in the Río de la Plata coast, Buenos Aires province. Since this, it showed a quick upstream invasion into the principals aquatic systems of the Plata Basin. Nevertheless, there is not a study about its invasion and distribution process in aquatic systems of Uruguay. We describe the new records of Limno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
18

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 12 publications
1
17
0
18
Order By: Relevance
“…Our results concerning L. fortunei's salinity tolerance coincided with what was observed in the golden mussel distribution in the La Plata river estuary, where colonies were registered in areas where the mean salinity does not exceed 3 ppt (DARRIGRAN & PASTORINO, 1995;DARRIGRAN, 2002;BRUGNOLI et al, 2005). …”
Section: Discussionsupporting
confidence: 87%
“…Our results concerning L. fortunei's salinity tolerance coincided with what was observed in the golden mussel distribution in the La Plata river estuary, where colonies were registered in areas where the mean salinity does not exceed 3 ppt (DARRIGRAN & PASTORINO, 1995;DARRIGRAN, 2002;BRUGNOLI et al, 2005). …”
Section: Discussionsupporting
confidence: 87%
“…In the Uruguay River, whose mouth is not far from La Plata River estuary, the first golden mussel record date from 2001 (Brugnoli et al, 2005). According to the authors, until 2003 the species distribution was limited by Salto Grande hydropower dam.…”
Section: Discussionmentioning
confidence: 99%
“…Damborenea and Penchaszadeh (2006) reported that the species manifested a high flexibility during its reproductive cycle and that its dispersion was favored by human activity (Darrigran and Ezcurra de Drago, 2000;Manzur et al, 2003;Avelar et al, 2004;Brugnoli et al, 2005;Belz et al, 2005). This invasive species exhibits a great plasticity with respect to environmental variables, and this characteristic has been confirmed from the results of the analysis of correlation by Pearson, which data indicate special relationships to the physicochemical parameters examined in this present study.…”
Section: Discussionmentioning
confidence: 99%